Community composition, relative abundance and habitat association of avian species in Apini and Dikuma forest patches, Awi Administrative Zone, Ethiopia - Genet, Yenew; Ejigu, Dessalegn (Ethiopian Journal of Science and Technology, 2025)
Study on community composition, relative abundance and habitat association of avifauna in Apini and Dikuma forest patches, Awi Administrative Zone, Ethiopia, was carried out from September 2013 to April 2014. The main objective of this study was to investigate diversity, relative abundance, and habitat association of avian species in the study area. Data were collected using point count method, and analyzed using Shannon Weiner index, Simpson´s diversity index and Sorensen´s coefficient. A total of 95 avian species belonging to 44 families and 11orders were identified. Among 95 bird species, 93 are residents, one is intra-African migrant and one is Palaearctic migrant, and of the 93 resident birds, seven are endemic to Ethiopia, and ten shared between Ethiopia and Eritrea. In the present study, 79 and 83 bird species were recorded during the wet and dry seasons, respectively. Dikuma forest patch had the highest avian diversity during the dry season (H´=3.84) and Apini had the lowest (H´=3.59) in the same season. Habitat association of birds among the vegetation strata showed the highest species similarity occurred between forest interior and forest edge (CC=0.65), followed by forest edge and shrub (CC=0.62), and the least was between forest interior and shrub (CC=0.3). Species richness and composition are important parameters to maintain stability and functioning of an ecosystem. To conserve the rich avian diversity of Apini and Dikuma forest patches, the anthropogenic disturbances in the area should be minimized.